Adaptive gene expression of alternative splicing variants of PGC-1α regulates whole-body energy metabolism - Kazuhiro Nomura; Shinichi Kinoshita; Nao Mizusaki; Yoko Senga; Tsutomu Sasaki; Tadahiro Kitamura; Hiroshi Sakaue; Aki Emi; Tetsuya Hosooka; Masahiro Matsuo; Hitoshi Okamura; Taku Amo; et al. (Molecular Metabolism, 2024)
The transcriptional coactivator PGC-1α has been implicated in the regulation of multiple metabolic processes. However, the previously reported metabolic phenotypes of mice deficient in PGC-1α have been inconsistent. PGC-1α exists as multiple isoforms, including variants transcribed from an alternative first exon. We show here that alternative PGC-1α variants are the main entity that increases PGC-1α during exercise. These variants, unlike the canonical isoform of PGC-1α, are robustly upregulated in human skeletal muscle after exercise. Furthermore, the extent of this upregulation correlates with oxygen consumption. Mice lacking these variants manifest impaired energy expenditure during exercise, leading to the development of obesity and hyperinsulinemia. The alternative variants are also upregulated in brown adipose tissue in response to cold exposure, and mice lacking these variants are intolerant of a cold environment. Our findings thus indicate that an increase in PGC-1α expression, attributable mostly to upregulation of alternative variants, is pivotal for adaptive enhancement of energy expenditure and heat production and thereby essential for the regulation of whole-body energy metabolism.